Ultrahigh molecular weight polyethylene as well as preparation method and application thereof

By using a supported dual-core catalyst in the preparation of ultra-high molecular weight polyethylene, the problems of low catalyst efficiency and single product use are solved, and the efficient preparation of multi-purpose ultra-high molecular weight polyethylene is achieved, improving the performance and processing of fibers sex.

CN119390879APending Publication Date: 2025-02-07QINGDAO CHENGZHI HUAQING CHEMICAL NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411731019.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art has problems such as low catalyst efficiency and single product use in the preparation of ultra-high molecular weight polyethylene, and has low performance and complex process in the preparation of fibers.

Method used

Using a supported binuclear catalyst, the binuclear structure formed by isopropyl titanate, zirconium tetrachloride and imidazole provides multiple active centers to increase the rate of ethylene polymerization, and control the polymerization reaction through triethylamine regulation and the action of support materials. selectivity.

Benefits of technology

The production efficiency and product performance of ultra-high molecular weight polyethylene is significantly improved, making it possible to be used in both production of sheets and fiber preparation, improving the use of a single material, and improving processing performance and impact resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of ultra-high molecular weight polyethylene production, in particular to ultra-high molecular weight polyethylene as well as a preparation method and application thereof. The UHMWPE is prepared by efficiently catalyzing ethylene polymerization through a supported binuclear catalyst. According to the preparation method disclosed by the invention, all conditions are controlled, so that the particle size distribution of the prepared ultra-high molecular weight polyethylene is obviously narrowed, and the processing performance of the product is greatly improved. Moreover, the prepared ultra-high molecular weight polyethylene can be used for producing ultra-high molecular weight polyethylene plates and can also be used for producing ultra-high molecular weight polyethylene fibers, so that the application and the processability of the ultra-high molecular weight polyethylene are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-high molecular weight polyethylene production, in particular to ultra-high molecular weight polyethylene and a preparation method and application thereof. Background Art

[0002] Ultra-high molecular weight polyethylene (UHMWPE) is a thermoplastic engineering plastic with excellent properties. Its average molecular weight is usually above 1 million. Compared with ordinary polyethylene, it has outstanding wear resistance, impact resistance, self-lubrication, chemical corrosion resistance, low temperature resistance and other characteristics. Due to these excellent properties, UHMWPE has shown great application potential in many fields, such as military protection, aerospace, marine engineering, medical equipment and sporting goods industries.

[0003] In terms of molding applications, molding grade UHMWPE needs to have good machinability and formability. For some large molded products, such as anti-wear liners in marine engineering, the material is required to be able to evenly fill the mold cavity during the molding process and have high density and strength after molding. In the field of UHMWPE fibers, the mechanical properties of the fibers, such as strength, modulus, and toughness, are extremely high. For example, in the field of aerospace, as a reinforcing fiber for composite materials, it must be able to withstand complex mechanical loads. This requires that in the preparation process of UHMWPE fibers, the microstructure and properties of the fibers must be precisely controlled through reasonable formulations and processes. In addition, the fiber production process also needs to consider production efficiency and cost to meet the needs of large-scale industrial production.

[0004] The existing technology can realize the preparation of ultra-high molecular weight polyethylene, but there are problems such as low catalyst efficiency and relatively single use of the product. When ultra-high molecular weight polyethylene is used to prepare ultra-high molecular weight polyethylene fiber, there are problems such as low fiber performance and complicated preparation process. Summary of the invention

[0005] In view of the above deficiencies in the prior art, the object of the present invention is to provide an ultra-high molecular weight polyethylene, which greatly improves the production efficiency and product performance by adding a supported binuclear catalyst.

[0006] Another object of the present invention is to provide a method for preparing ultra-high molecular weight polyethylene, which has a simple process and relatively mild production conditions and is conducive to industrial production.

[0007] The third object of the present invention is to provide an application of ultra-high molecular weight polyethylene, which can be used to produce ultra-high molecular weight polyethylene sheets and ultra-high molecular weight polyethylene fibers, greatly improving the use of a single ultra-high molecular weight polyethylene. The prepared ultra-high molecular weight polyethylene sheets have good mechanical properties, and the ultra-high molecular weight polyethylene fibers have the advantages of high tensile strength, smooth surface, easy processing, strong impact resistance, etc.

[0008] The present invention is achieved by adopting the following technical solutions: The method for preparing the ultra-high molecular weight polyethylene comprises the following steps: (1) Seal the reactor and replace the air in the reactor with nitrogen, repeat the replacement 3-5 times, and add 65-70% of the reactor volume of hexane into the reactor in advance; (2) Add the supported binuclear catalyst and methylaluminoxane into the reactor under stirring at 450-540 rpm; the amount of hexane added is 60-80% of the volume of the reactor; (3) Raise the temperature to 73-78°C, introduce ethylene gas through the feed port, maintain the pressure in the reactor at 0.4-0.8 MPaG, and continue the reaction for 4-5 hours; (4) After the reaction is completed, stop introducing ethylene and cool the reactor at a rate of 10-30°C / h. After the reactor temperature drops to room temperature, discharge the reaction product into a separation device and separate the ultra-high molecular weight polyethylene from the hexane by filtration. (5) Dry the separated ultra-high molecular weight polyethylene in a vacuum drying oven at a drying temperature of 65-75°C for a drying time of 18-20 hours to obtain pure ultra-high molecular weight polyethylene.

[0009] The method for preparing the supported binuclear catalyst comprises the following steps: a. Under nitrogen atmosphere, stir the mixture in a mass ratio of imidazole to toluene of 1:(6-8) to completely dissolve the imidazole to form a uniform solution, then add isopropyl titanate and zirconium tetrachloride. During the process, control the temperature at 25-28°C and continue stirring for 4-5 hours. The mass ratio of isopropyl titanate to zirconium tetrachloride is (1-2):1. The purpose of stirring is to allow the metal precursor (the sum of isopropyl titanate and zirconium tetrachloride) to fully coordinate with the imidazole. b. triethylamine is added to the solution obtained in step a, the temperature is raised to 45-55 ° C, and stirring is continued for 2-4h. The amount of triethylamine added is 0.2-0.4 times the total mass of isopropyl titanate and zirconium tetrachloride; c. Add methylaluminoxane to the reaction system obtained in step b, continue stirring, then add silica, raise the temperature to 65-75°C, react for 4-8h under stirring at a stirring speed of 350-450rpm to fully activate the catalyst precursor and load it on the silica; d. After the reaction is completed, the reaction solution is cooled to room temperature, filtered under nitrogen protection, the solid product is washed 3-5 times with dry n-hexane, and the solid catalyst is dried in a vacuum drying oven at 55-65°C for 8-10h to obtain a supported binuclear catalyst.

[0010] In the step c, before adding silica, it needs to undergo the following treatment: the silica is vacuum dried and calcined at 560-820°C for 2-3h to increase its specific surface area, make the pore structure more regular, and provide more active sites for the subsequent loading process.

[0011] In the step (2), the molar ratio of Al in methylaluminoxane to the metal in the supported binuclear catalyst is (80-120):1; in the step c, the amount of methylaluminoxane added is 8-13 times the total mass of isopropyl titanate and zirconium tetrachloride, the silica is spherical, and the amount of silica added is 18-22% of the total mass of the catalyst reaction system.

[0012] The purity of the isopropyl titanate and zirconium tetrachloride is higher than 99%, and the purity of imidazole is higher than 98%.

[0013] The ultra-high molecular weight polyethylene is prepared by the above-mentioned preparation method of ultra-high molecular weight polyethylene.

[0014] The ultra-high molecular weight polyethylene is used for the preparation of ultra-high molecular weight polyethylene sheets and ultra-high molecular weight polyethylene fibers.

[0015] The method for preparing the ultra-high molecular weight polyethylene sheet comprises the following steps: ① Add ultra-high molecular weight polyethylene, antioxidant 1010 and zinc stearate into a mixer and mix them. The mixer speed is 900-1300rpm and the mixing time is 10-20min. The amount of antioxidant 1010 added is 0.2-0.4% of the mass of ultra-high molecular weight polyethylene, and the amount of zinc stearate added is 0.5-0.8% of the mass of ultra-high molecular weight polyethylene. ② Use a cold press molding machine for preforming, press the raw materials mixed in step ① into a blank of the desired shape, the density of the blank is 0.9-1.0g / cm³, the applied pressure is 8-10MPa, and the holding time is 5-10min; ③ Use a hot press for molding, the molding temperature is 180-220℃, the molding pressure is 10-30MPa, and the molding time is 3-5min per millimeter of thickness; ④ After the molding is completed, the mold is cooled by air cooling, and the cooling rate is controlled at 5-10℃ / min. When the temperature of the product drops to 65-75℃, demolding is carried out to obtain an ultra-high molecular weight polyethylene sheet.

[0016] The method for preparing the ultra-high molecular weight polyethylene fiber comprises the following steps: Ⅰ. Add ultra-high molecular weight polyethylene, 4,4'-thiol methylene diphenol, 2,4-dimethylthiophenol, calcium stearate, titanate coupling agent, tri(2-methylpropyl) phosphate, polytetrafluoroethylene, 4-cyanostyrene, polypropylene and solvent decalin into a high-speed mixer and mix at a mixing speed of 1450-1550 rpm for 35-45 minutes; Ⅱ. The raw materials mixed in step Ⅰ are placed in a twin-screw extruder for extrusion, the extruder temperature is controlled at 213-218 ° C, the screw speed is 48-55rpm, and then filtered through a filter, and then fed into the spinning box by a metering pump to obtain a spinning solution, and the spinning solution temperature is controlled at 213-218 ° C; Ⅲ. The spinning solution in step Ⅱ is ejected from the spinneret hole to form a fiber, the spinneret aperture is 0.3-0.4mm, the spinning speed is 210-280m / min, the drafting multiple is 18-25 times, the drafting temperature is 152-158°C, and the decalin is blown off the fiber with 80°C nitrogen, and the fiber enters the hot air box for drying; IV. The fiber obtained in step III is stretched on a stretching machine at a stretching temperature of 145-155°C and a stretching ratio of 42-55 times to obtain an ultra-high molecular weight polyethylene fiber.

[0017] In the step I, the mass fractions of the raw materials are: 100 parts of ultra-high molecular weight polyethylene; 0.5-1.3 parts of 4,4'-thiol methylene diphenol; 0.8-1.2 parts of 2,4-dimethylthiophenol; 1-3 parts of calcium stearate; 0.3-0.8 parts of titanate coupling agent; 2-3 parts of tri(2-methylpropyl) phosphate; 3-5 parts of polytetrafluoroethylene; 0.8-1.4 parts of 4-cyanostyrene; 8-12 parts of polypropylene; and 350-420 parts of decalin.

[0018] A solvent recovery device is arranged above the twin-screw extruder, and the titanate coupling agent is one of triisostearyl isopropyl titanate or tetrabutyl titanate.

[0019] The binuclear structure formed by isopropyl titanate, zirconium tetrachloride and imidazole provides multiple active centers, which can efficiently catalyze ethylene polymerization, increase the polymerization reaction rate, and improve the processability of ultra-high molecular weight polyethylene. At the same time, through the regulation of triethylamine and the role of the carrier material, the selectivity of the polymerization reaction can be better controlled, which is suitable for the preparation of high-performance fibers. As a carrier material, silica not only provides physical support for the catalyst, but also improves the thermal stability and anti-poisoning ability of the catalyst. The porous structure of the carrier can effectively disperse the active components of the catalyst and prevent them from agglomerating, thereby extending the service life of the catalyst.

[0020] Both 4,4'-thiol methylenediphenol and 2,4-dimethylthiophenol contain active functional groups (phenolic hydroxyl and thiol groups) that interact with UHMWPE molecular chains. On the one hand, they can increase the physical crosslinking points between molecular chains and limit the slippage of molecular chains, thereby improving the tensile strength of the fiber; on the other hand, these functional groups can capture free radicals, improve the antioxidant properties of the fiber, and extend the service life of the fiber. Phenolic hydroxyl and thiol groups can form hydrogen bonds or chemical bonds with a small number of active sites on the UHMWPE molecular chain (such as double bonds at the end or free radical sites generated by the decomposition of peroxides). When stretched by external forces, this interaction can effectively transmit stress and prevent rapid slippage and breakage of molecular chains. At the same time, in an oxidative environment, they can preferentially react with free radicals to terminate the oxidation chain reaction and play an anti-aging role.

[0021] Calcium stearate mainly plays an internal lubricating role, while polytetrafluoroethylene (PTFE) has both external lubrication and wear resistance. The combination of the two can significantly reduce the friction coefficient of the fiber during processing, improve the processability of the fiber, and greatly enhance the wear resistance of the finished fiber. The long-chain fatty acid radical of calcium stearate can play an isolating and lubricating role between UHMWPE molecular chains, reducing the friction between molecular chains and between the fiber and processing equipment. PTFE has an extremely low friction coefficient, and its particles can form a lubricating and wear-resistant coating on the fiber surface. During processing, PTFE particles can roll between the fiber and the equipment, further reducing friction; during use, this coating can effectively resist external friction and reduce wear on the fiber surface.

[0022] Titanate coupling agent can improve the interfacial compatibility between UHMWPE and other additives (such as 4-cyanostyrene, polypropylene, etc.). It can enhance the binding force between different components and make each additive more evenly dispersed in the UHMWPE matrix, thereby improving the comprehensive performance of the fiber. Titanate coupling agent molecules have two different functional groups. One end can react chemically with the active groups (such as hydroxyl) on the UHMWPE molecular chain, and the other end can interact with the functional groups on the surface of other additives (such as cyano of 4-cyanostyrene, carbonyl of polypropylene, etc.). Through this bridging effect, the chemical connection between different components is strengthened, and the stability and uniformity of the system are improved. Tri(2-methylpropyl) phosphate can improve the flame retardant properties of the fiber, and 4-cyanostyrene can enhance the strength of the fiber. When both exist at the same time, while improving the strength of the fiber, they can also give the fiber a certain flame retardant property. Tri(2-methylpropyl) phosphate can decompose at high temperature to produce substances such as phosphoric acid, which can form a protective film on the fiber surface to prevent oxygen from contacting the fiber, thereby playing a flame retardant role. 4-Cyanostyrene can increase the rigidity and strength of the molecular chain through interaction with the UHMWPE molecular chain (such as π-π stacking or copolymerization). When the fiber is subjected to external force, this interaction can effectively share the stress and improve the load-bearing capacity of the fiber.

[0023] Polypropylene (PP) can improve the processing performance and toughness of UHMWPE. Since the molecular chain structure of PP is relatively regular and has a certain degree of flexibility, blending with UHMWPE can reduce the melt viscosity of the system, improve processability, and improve the toughness of the fiber, making it less likely to break when impacted. PP molecular chains can be entangled with UHMWPE molecular chains. During the processing, the presence of PP can improve the fluidity of the entire system, making it easier to perform processing operations such as melt spinning. When the fiber is impacted by external force, the PP molecular chain can absorb part of the energy through its own deformation, preventing the UHMWPE molecular chain from breaking due to excessive force, thereby improving the toughness of the fiber.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The ultra-high molecular weight polyethylene prepared by the present invention provides multiple active centers through the binuclear structure formed by isopropyl titanate, zirconium tetrachloride and imidazole, which can efficiently catalyze ethylene polymerization and increase the polymerization reaction rate.

[0025] (2) The particle size distribution of the ultra-high molecular weight polyethylene obtained by the preparation method of the present invention is significantly narrowed, which greatly improves the processing performance of the product.

[0026] (3) The method for preparing ultra-high molecular weight polyethylene adopted in the present invention has a simple process and relatively mild production conditions, which is conducive to industrial production.

[0027] (4) The ultra-high molecular weight polyethylene prepared by the present invention can be used to produce ultra-high molecular weight polyethylene sheets and ultra-high molecular weight polyethylene fibers, which greatly improves the use of ultra-high molecular weight polyethylene and greatly improves the processability. The prepared ultra-high molecular weight polyethylene sheets have good mechanical properties, and the ultra-high molecular weight polyethylene fibers have the advantages of high tensile strength, smooth surface, easy processing, strong impact resistance, etc. DETAILED DESCRIPTION

[0028] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail.

[0029] Example 1 The preparation method of the supported binuclear catalyst comprises the following steps: a. Under a nitrogen atmosphere, the material is stirred in a mass ratio of imidazole to toluene of 1:7 to completely dissolve the imidazole to form a uniform solution, and then isopropyl titanate and zirconium tetrachloride are added thereto. The temperature is controlled at 26°C during the process, and stirring is continued for 4 hours. The mass ratio of isopropyl titanate to zirconium tetrachloride is 1:1; b. triethylamine was added to the solution obtained in step a, the temperature was raised to 50 ° C, and stirring was continued for 3h. The amount of triethylamine added was 0.3 times the total mass of isopropyl titanate and zirconium tetrachloride; c. Methylaluminoxane was added to the reaction system obtained in step b, and stirring was continued. Then, silica was added, and the temperature was raised to 70°C. The reaction was stirred for 6 hours at a stirring speed of 400 rpm to fully activate the catalyst precursor and load it on the silica. d. After the reaction, the reaction solution was cooled to room temperature and filtered under nitrogen protection. The solid product was washed four times with dry n-hexane. The solid catalyst was dried in a vacuum drying oven at 60° C. for 9 h to obtain a supported binuclear catalyst.

[0030] In step c, before adding silicon dioxide, it needs to undergo the following treatment: the silicon dioxide is dried and calcined in vacuum at 700° C. for 3 h.

[0031] The amount of methylaluminoxane added is 10 times the total mass of isopropyl titanate and zirconium tetrachloride, the silicon dioxide is spherical, and the amount of silicon dioxide added is 20% of the total mass of the catalyst reaction system. The purity of isopropyl titanate and zirconium tetrachloride is 99.5%, and the purity of imidazole is 99%.

[0032] The method for preparing ultra-high molecular weight polyethylene comprises the following steps: (1) Seal the reactor and replace the air in the reactor with nitrogen, repeat the replacement 4 times, and add 68% of the reactor volume of hexane into the reactor in advance; (2) Adding the supported binuclear catalyst and methylaluminoxane into the reactor under stirring at 500 rpm; the molar ratio of Al in methylaluminoxane to the metal in the supported binuclear catalyst is 100:1; (3) Raise the temperature to 75°C, introduce ethylene gas through the feed port, maintain the pressure in the reactor at 0.6 MPaG, and continue the reaction for 4 hours; (4) After the reaction is completed, stop introducing ethylene and cool the reactor at a rate of 20°C / h. After the reactor temperature drops to room temperature, discharge the reaction product into a separation device and separate the ultra-high molecular weight polyethylene from the hexane by filtration. (5) The separated ultra-high molecular weight polyethylene was dried in a vacuum drying oven at a temperature of 70°C for 19 hours to obtain pure ultra-high molecular weight polyethylene. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene was 4.5 million.

[0033] Example 2 The preparation method of the supported binuclear catalyst comprises the following steps: a. Under a nitrogen atmosphere, the imidazole and toluene were stirred at a mass ratio of 1:8 to completely dissolve the imidazole to form a uniform solution, and then isopropyl titanate and zirconium tetrachloride were added thereto. The temperature was controlled at 28°C during the process, and stirring was continued for 5 hours. The mass ratio of isopropyl titanate to zirconium tetrachloride was 2:1. b. triethylamine was added to the solution obtained in step a, the temperature was raised to 55 ° C, and stirring was continued for 4h. The amount of triethylamine added was 0.4 times the total mass of isopropyl titanate and zirconium tetrachloride; c. Methylaluminoxane was added to the reaction system obtained in step b, and stirring was continued. Then, silica was added, and the temperature was raised to 75°C. The reaction was stirred for 8 hours at a stirring speed of 450 rpm to fully activate the catalyst precursor and load it on the silica. d. After the reaction was completed, the reaction solution was cooled to room temperature and filtered under nitrogen protection. The solid product was washed 5 times with dry n-hexane. The solid catalyst was dried in a vacuum drying oven at 65° C. for 10 h to obtain a supported binuclear catalyst.

[0034] In step c, before adding silicon dioxide, it needs to undergo the following treatment: the silicon dioxide is vacuum dried and calcined at 820° C. for 2 h, and then immersed in a zirconium nitrate solution for 3 h.

[0035] The amount of methylaluminoxane added is 13 times the total mass of isopropyl titanate and zirconium tetrachloride, the silicon dioxide is spherical, and the amount of silicon dioxide added is 22% of the total mass of the catalyst reaction system. The purity of isopropyl titanate and zirconium tetrachloride is 99.6%, and the purity of imidazole is 99%.

[0036] The method for preparing ultra-high molecular weight polyethylene comprises the following steps: (1) Seal the reactor and replace the air in the reactor with nitrogen, repeat the replacement 5 times, and add 70% of the reactor volume of hexane into the reactor in advance; (2) Adding the supported binuclear catalyst and methylaluminoxane into the reactor under stirring at 540 rpm; the molar ratio of Al in methylaluminoxane to the metal in the supported binuclear catalyst is 120:1; (3) Raise the temperature to 78°C, introduce ethylene gas through the feed port, maintain the pressure in the reactor at 0.8 MPaG, and continue the reaction for 5 hours; (4) After the reaction is completed, stop introducing ethylene and cool the reactor at a rate of 30°C / h. After the reactor temperature drops to room temperature, discharge the reaction product into a separation device and separate the ultra-high molecular weight polyethylene from the hexane by filtration. (5) The separated ultra-high molecular weight polyethylene was dried in a vacuum drying oven at a temperature of 75°C for 20 hours to obtain pure ultra-high molecular weight polyethylene. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene was 4.8 million.

[0037] Example 3 The preparation method of the supported binuclear catalyst comprises the following steps: a. Under a nitrogen atmosphere, the material was stirred in a mass ratio of imidazole to toluene of 1: 6 to completely dissolve the imidazole to form a uniform solution, and then isopropyl titanate and zirconium tetrachloride were added thereto. The temperature was controlled at 25 ° C during the process and stirring was continued for 4 hours. The mass ratio of isopropyl titanate to zirconium tetrachloride was 1: 1; b. triethylamine was added to the solution obtained in step a, the temperature was raised to 45 ° C, and stirring was continued for 2h. The amount of triethylamine added was 0.2 times the total mass of isopropyl titanate and zirconium tetrachloride; c. Methylaluminoxane was added to the reaction system obtained in step b, and stirring was continued. Then, silica was added, and the temperature was raised to 65°C. The reaction was stirred for 4 hours at a stirring speed of 350 rpm to fully activate the catalyst precursor and load it on the silica. d. After the reaction was completed, the reaction solution was cooled to room temperature and filtered under nitrogen protection. The solid product was washed three times with dry n-hexane. The solid catalyst was dried in a vacuum drying oven at 55° C. for 8 h to obtain a supported binuclear catalyst.

[0038] In step c, before adding silicon dioxide, it needs to undergo the following treatment: the silicon dioxide is dried and calcined at 560° C. in vacuum for 3 h.

[0039] The amount of methylaluminoxane added is 8 times the total mass of isopropyl titanate and zirconium tetrachloride, the silicon dioxide is spherical, and the amount of silicon dioxide added is 18-22% of the total mass of the catalyst reaction system. The purity of isopropyl titanate and zirconium tetrachloride is 99.1%, and the purity of imidazole is 98.5%.

[0040] The method for preparing ultra-high molecular weight polyethylene comprises the following steps: (1) Seal the reactor and replace the air in the reactor with nitrogen, repeat the replacement three times, and add 65% of the reactor volume of hexane into the reactor in advance; (2) Adding the supported binuclear catalyst and methylaluminoxane into the reactor under stirring at 450 rpm; the molar ratio of Al in methylaluminoxane to the metal in the supported binuclear catalyst is 80:1; (3) Raise the temperature to 73°C, introduce ethylene gas through the feed port, maintain the pressure in the reactor at 0.4 MPaG, and continue the reaction for 4 hours; (4) After the reaction is completed, stop introducing ethylene and cool the reactor at a rate of 10°C / h. After the reactor temperature drops to room temperature, discharge the reaction product into a separation device and separate the ultra-high molecular weight polyethylene from the hexane by filtration. (5) The separated ultra-high molecular weight polyethylene was dried in a vacuum drying oven at a temperature of 65°C for 18 hours to obtain pure ultra-high molecular weight polyethylene. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene was 4.3 million.

[0041] Example 4 The preparation method of the supported binuclear catalyst comprises the following steps: a. Under a nitrogen atmosphere, the material is stirred in a mass ratio of imidazole to toluene of 1:7 to completely dissolve the imidazole to form a uniform solution, and then isopropyl titanate and zirconium tetrachloride are added thereto. The temperature is controlled at 26°C during the process, and stirring is continued for 4 hours. The mass ratio of isopropyl titanate to zirconium tetrachloride is 1:1; b. triethylamine was added to the solution obtained in step a, the temperature was raised to 50 ° C, and stirring was continued for 3h. The amount of triethylamine added was 0.3 times the total mass of isopropyl titanate and zirconium tetrachloride; c. Methylaluminoxane was added to the reaction system obtained in step b, and stirring was continued. Then, silica was added, and the temperature was raised to 70°C. The reaction was stirred for 6 hours at a stirring speed of 400 rpm to fully activate the catalyst precursor and load it on the silica. d. After the reaction, the reaction solution was cooled to room temperature and filtered under nitrogen protection. The solid product was washed four times with dry n-hexane. The solid catalyst was dried in a vacuum drying oven at 60° C. for 9 h to obtain a supported binuclear catalyst.

[0042] In step c, before adding silicon dioxide, it needs to undergo the following treatment: the silicon dioxide is dried and calcined at 580° C. in vacuum for 3 h.

[0043] The amount of methylaluminoxane added is 10 times the total mass of isopropyl titanate and zirconium tetrachloride, the silicon dioxide is spherical, and the amount of silicon dioxide added is 18-22% of the total mass of the catalyst reaction system. The purity of isopropyl titanate and zirconium tetrachloride is 99.5%, and the purity of imidazole is 99%.

[0044] The method for preparing ultra-high molecular weight polyethylene comprises the following steps: (1) Seal the reactor and replace the air in the reactor with nitrogen, repeat the replacement three times, and add 65% of the reactor volume of hexane into the reactor in advance; (2) Adding the supported binuclear catalyst and methylaluminoxane into the reactor under stirring at 450 rpm; the molar ratio of Al in methylaluminoxane to the metal in the supported binuclear catalyst is 120:1; (3) Raise the temperature to 73°C, introduce ethylene gas through the feed port, maintain the pressure in the reactor at 0.4 MPaG, and continue the reaction for 4 hours; (4) After the reaction is completed, stop introducing ethylene and cool the reactor at a rate of 10°C / h. After the reactor temperature drops to room temperature, discharge the reaction product into a separation device and separate the ultra-high molecular weight polyethylene from the hexane by filtration. (5) The separated ultra-high molecular weight polyethylene was dried in a vacuum drying oven at a temperature of 65°C for 18 hours to obtain pure ultra-high molecular weight polyethylene. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene was 4.4 million.

[0045] Example 5 The preparation method of the supported binuclear catalyst comprises the following steps: a. Under a nitrogen atmosphere, the imidazole and toluene were stirred at a mass ratio of 1:8 to completely dissolve the imidazole to form a uniform solution, and then isopropyl titanate and zirconium tetrachloride were added thereto. The temperature was controlled at 28°C during the process, and stirring was continued for 5 hours. The mass ratio of isopropyl titanate to zirconium tetrachloride was 2:1. b. triethylamine was added to the solution obtained in step a, the temperature was raised to 55 ° C, and stirring was continued for 4h. The amount of triethylamine added was 0.4 times the total mass of isopropyl titanate and zirconium tetrachloride; c. Methylaluminoxane was added to the reaction system obtained in step b, and stirring was continued. Then, silica was added, and the temperature was raised to 75°C. The reaction was stirred for 8 hours at a stirring speed of 450 rpm to fully activate the catalyst precursor and load it on the silica. d. After the reaction was completed, the reaction solution was cooled to room temperature and filtered under nitrogen protection. The solid product was washed 5 times with dry n-hexane. The solid catalyst was dried in a vacuum drying oven at 65° C. for 10 h to obtain a supported binuclear catalyst.

[0046] In step c, before adding silicon dioxide, it needs to undergo the following treatment: the silicon dioxide is dried and calcined at 780° C. in vacuum for 3 h.

[0047] The amount of methylaluminoxane added is 13 times the total mass of isopropyl titanate and zirconium tetrachloride, the silicon dioxide is spherical, and the amount of silicon dioxide added is 18-22% of the total mass of the catalyst reaction system. The purity of isopropyl titanate and zirconium tetrachloride is 99.6%, and the purity of imidazole is 99%.

[0048] The method for preparing ultra-high molecular weight polyethylene comprises the following steps: (1) Seal the reactor and replace the air in the reactor with nitrogen, repeat the replacement 4 times, and add 68% of the reactor volume of hexane into the reactor in advance; (2) Adding the supported binuclear catalyst and methylaluminoxane into the reactor under stirring at 500 rpm; the molar ratio of Al in methylaluminoxane to the metal in the supported binuclear catalyst is 90:1; (3) Raise the temperature to 75°C, introduce ethylene gas through the feed port, maintain the pressure in the reactor at 0.6 MPaG, and continue the reaction for 4 hours; (4) After the reaction is completed, stop introducing ethylene and cool the reactor at a rate of 20°C / h. After the reactor temperature drops to room temperature, discharge the reaction product into a separation device and separate the ultra-high molecular weight polyethylene from the hexane by filtration. (5) The separated ultra-high molecular weight polyethylene was dried in a vacuum drying oven at 70°C for 19 hours to obtain pure ultra-high molecular weight polyethylene. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene was 4.6 million.

[0049] Comparative Example 1 Compared with Example 1, the difference is that when preparing the supported binuclear catalyst, isopropyl titanate is not added, and triethylamine is replaced by toluene. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene is 3.5 million.

[0050] Comparative Example 2 Compared with Example 2, the difference is that when preparing the supported binuclear catalyst, zirconium tetrachloride and methylaluminoxane are not added. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene is 3.6 million.

[0051] Comparative Example 3 Compared with Example 1, the difference is that silicon dioxide is not added when preparing the supported binuclear catalyst. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene is 3.1 million.

[0052] Comparative Example 4 Compared with Example 3, the difference is that when preparing the ultra-high molecular weight polyethylene, after the reaction is completed, the temperature is naturally cooled. After testing, the relative molecular mass of the obtained ultra-high molecular weight polyethylene is 4.1 million.

[0053] The test data of Examples 1-5 and Comparative Examples 1-4 are shown in Table 1.

[0054] Table 1 Test data of Examples 1-5 and Comparative Examples 1-4

[0055] From the above data, we can see that isopropyl titanate and zirconium tetrachloride are very important for catalytic activity, and the binuclear structure can significantly improve the catalytic efficiency; triethylamine and carrier materials can better control the selectivity of the polymerization reaction.

[0056] Application Example 1 The method for preparing an ultra-high molecular weight polyethylene sheet comprises the following steps: ① The ultra-high molecular weight polyethylene obtained in Example 1, antioxidant 1010 and zinc stearate were added to a mixer and mixed at a mixer speed of 1100 rpm for 15 min. The amount of antioxidant 1010 added was 0.3% of the mass of the ultra-high molecular weight polyethylene, and the amount of zinc stearate added was 0.6% of the mass of the ultra-high molecular weight polyethylene. ② Use a cold press molding machine for preforming, press the raw materials mixed in step ① into a blank of the desired shape, the density of the blank is 1.0g / cm³, the applied pressure is 9MPa, and the holding time is 8min; ③ Use a hot press for molding, the molding temperature is 200℃, the molding pressure is 20MPa, and the molding time is 4min per millimeter of thickness; ④ After the molding is completed, the mold is cooled by air cooling, and the cooling rate is controlled at 8℃ / min. When the temperature of the product drops to 70℃, demolding is carried out to obtain an ultra-high molecular weight polyethylene sheet.

[0057] Application Example 2 The method for preparing an ultra-high molecular weight polyethylene sheet comprises the following steps: ① The ultra-high molecular weight polyethylene obtained in Example 2, antioxidant 1010 and zinc stearate were added to a mixer and mixed at a mixer speed of 1300 rpm for 20 min. The amount of antioxidant 1010 added was 0.4% of the mass of the ultra-high molecular weight polyethylene, and the amount of zinc stearate added was 0.8% of the mass of the ultra-high molecular weight polyethylene. ② Use a cold press molding machine for preforming, press the raw materials mixed in step ① into a blank of the desired shape, the density of the blank is 1.0g / cm³, the applied pressure is 10MPa, and the holding time is 10min; ③ Use a hot press for molding, the molding temperature is 220℃, the molding pressure is 30MPa, and the molding time is 5min per millimeter of thickness; ④ After the molding is completed, the mold is cooled by air cooling, and the cooling rate is controlled at 10℃ / min. When the temperature of the product drops to 75℃, demolding is carried out to obtain an ultra-high molecular weight polyethylene sheet.

[0058] Application Example 3 The method for preparing an ultra-high molecular weight polyethylene sheet comprises the following steps: ① The ultra-high molecular weight polyethylene obtained in Example 3, antioxidant 1010 and zinc stearate were added into a mixer and mixed at a mixer speed of 900 rpm for 10 min. The amount of antioxidant 1010 added was 0.2% of the mass of the ultra-high molecular weight polyethylene, and the amount of zinc stearate added was 0.5% of the mass of the ultra-high molecular weight polyethylene. ② Use a cold press molding machine for preforming, press the raw materials mixed in step ① into a blank of the desired shape, the density of the blank is 0.9g / cm³, the applied pressure is 8MPa, and the holding time is 5min; ③ Use a hot press for molding, the molding temperature is 180℃, the molding pressure is 10MPa, and the molding time is 3min per millimeter of thickness; ④ After the molding is completed, the mold is cooled by air cooling, and the cooling rate is controlled at 5℃ / min. When the temperature of the product drops to 65℃, demolding is carried out to obtain an ultra-high molecular weight polyethylene sheet.

[0059] Application Example 4 The method for preparing ultra-high molecular weight polyethylene fiber comprises the following steps: Ⅰ. The ultra-high molecular weight polyethylene obtained in Example 1, 4,4'-thiol methylene diphenol, 2,4-dimethylthiophenol, calcium stearate, titanate coupling agent, tri(2-methylpropyl) phosphate, polytetrafluoroethylene, 4-cyanostyrene, polypropylene and solvent decalin were added to a high-speed mixer and mixed at a mixing speed of 1500 rpm for 40 minutes; Ⅱ. The raw materials mixed in step Ⅰ are placed in a twin-screw extruder for extrusion, the extruder temperature is controlled at 215 ° C, the screw speed is 52 rpm, and then filtered through a filter, and then the metering pump enters the spinning box to obtain a spinning solution, and the spinning solution temperature is controlled at 215 ° C; Ⅲ. The spinning solution in step Ⅱ is ejected from the spinneret hole to form a fiber, the spinneret aperture is 0.4mm, the spinning speed is 250m / min, the draft ratio is 22 times, the drafting temperature is 155 ℃, and the decalin is blown off the fiber with 80 ℃ nitrogen, and the fiber enters the hot air oven for drying; IV. The fiber obtained in step III was stretched on a stretching machine at a stretching temperature of 150°C and a stretching ratio of 50 times to obtain an ultra-high molecular weight polyethylene fiber.

[0060] The mass fractions of the raw materials are as follows: 100 parts of ultra-high molecular weight polyethylene; 0.8 parts of 4,4'-mercaptimethylene diphenol; 1 part of 2,4-dimethylthiophenol; 2 parts of calcium stearate; 0.5 parts of titanate coupling agent; 3 parts of tri(2-methylpropyl) phosphate; 4 parts of polytetrafluoroethylene; 1.1 parts of 4-cyanostyrene; 10 parts of polypropylene; 380 parts of decahydronaphthalene. A solvent recovery device is provided above the twin-screw extruder, and the titanate coupling agent is triisostearoyl isopropyl titanate.

[0061] Application Example 5 The method for preparing ultra-high molecular weight polyethylene fiber comprises the following steps: Ⅰ. The ultra-high molecular weight polyethylene obtained in Example 2, 4,4'-thiol methylene diphenol, 2,4-dimethylthiophenol, calcium stearate, titanate coupling agent, tri(2-methylpropyl) phosphate, polytetrafluoroethylene, 4-cyanostyrene, polypropylene and solvent decalin were added to a high-speed mixer and mixed at a mixing speed of 1450 rpm for 35 minutes; Ⅱ. The raw materials mixed in step Ⅰ are placed in a twin-screw extruder for extrusion, the extruder temperature is controlled at 213 ° C, the screw speed is 48 rpm, and then filtered through a filter, and then enter the spinning box by a metering pump to obtain a spinning solution, and the spinning solution temperature is controlled at 213 ° C; Ⅲ. The spinning solution in step Ⅱ is ejected from the spinneret hole to form a fiber, the spinneret aperture is 0.3mm, the spinning speed is 210m / min, the draft ratio is 18 times, the drafting temperature is 152 ℃, and the decalin is blown off the fiber with 80 ℃ nitrogen, and the fiber enters the hot air box for drying; IV. The fiber obtained in step III was stretched on a stretching machine at a stretching temperature of 145°C and a stretching ratio of 42 times to obtain an ultra-high molecular weight polyethylene fiber.

[0062] The mass fraction of each raw material is as follows: 100 parts of ultra-high molecular weight polyethylene; 0.5 parts of 4,4'-mercaptimethylene diphenol; 0.8 parts of 2,4-dimethylthiophenol; 1 part of calcium stearate; 0.3 parts of titanate coupling agent; 2 parts of tri(2-methylpropyl) phosphate; 3 parts of polytetrafluoroethylene; 0.8 parts of 4-cyanostyrene; 8 parts of polypropylene; 350 parts of decalin. A solvent recovery device is provided above the twin-screw extruder, and the titanate coupling agent is tetrabutyl titanate.

[0063] Application Example 6 The method for preparing ultra-high molecular weight polyethylene fiber comprises the following steps: Ⅰ. The ultra-high molecular weight polyethylene obtained in Example 3, 4,4'-thiol methylene diphenol, 2,4-dimethylthiophenol, calcium stearate, titanate coupling agent, tri(2-methylpropyl) phosphate, polytetrafluoroethylene, 4-cyanostyrene, polypropylene and solvent decalin were added to a high-speed mixer and mixed at a mixing speed of 1550 rpm for 45 minutes; Ⅱ. The raw materials mixed in step Ⅰ are placed in a twin-screw extruder for extrusion, the extruder temperature is controlled at 218 ° C, the screw speed is 55 rpm, and then filtered through a filter, and then enter the spinning box by a metering pump to obtain a spinning solution, and the spinning solution temperature is controlled at 218 ° C; Ⅲ. The spinning solution in step Ⅱ is ejected from the spinneret hole to form a fiber, the spinneret aperture is 0.4mm, the spinning speed is 280m / min, the draft ratio is 25 times, the drafting temperature is 158 ℃, and the decalin is blown off the fiber with 80 ℃ nitrogen, and the fiber enters the hot air box for drying; IV. The fiber obtained in step III was stretched on a stretching machine at a stretching temperature of 155°C and a stretching ratio of 55 times to obtain an ultra-high molecular weight polyethylene fiber.

[0064] The mass fraction of each raw material is as follows: 100 parts of ultra-high molecular weight polyethylene; 1.3 parts of 4,4'-mercaptimethylene diphenol; 1.2 parts of 2,4-dimethylthiophenol; 3 parts of calcium stearate; 0.8 parts of titanate coupling agent; 3 parts of tri(2-methylpropyl) phosphate; 5 parts of polytetrafluoroethylene; 1.4 parts of 4-cyanostyrene; 12 parts of polypropylene; 420 parts of decahydronaphthalene. A solvent recovery device is provided above the twin-screw extruder, and the titanate coupling agent is triisostearoyl isopropyl titanate.

[0065] Application Comparative Example 1 Compared with Application Example 1, the difference is that: antioxidant 1010 and zinc stearate are not added to the raw materials.

[0066] Application Comparative Example 2 Compared with Application Example 2, the difference is that after the molding is completed, natural cooling is performed.

[0067] Application Comparative Example 3 Compared with Application Example 4, the difference is that: 4,4'-thiol methylenediphenol and 2,4-dimethylthiophenol are not added to the raw materials.

[0068] Application Comparative Example 4 Compared with Application Example 5, the difference is that calcium stearate and tetrabutyl titanate are not added to the raw materials.

[0069] Application Comparative Example 5 Compared with Application Example 4, the difference is that no 4-cyanostyrene and polypropylene are added to the raw materials.

[0070] The test data of application examples 1-3 and application comparative examples 1-2 are shown in Table 2.

[0071] The test data of application examples 4-6 and application comparative examples 3-5 are shown in Table 3.

[0072] Table 2 Test data of application examples 1-3 and application comparative examples 1-2

[0073] Table 3 Test data of application examples 4-6 and application comparative examples 3-5

[0074] From the above data, it can be seen that 4,4'-thiomethanodiphenol, 2,4-dimethylthiophenol, calcium stearate and titanate coupling agent have a great influence on the performance of ultra-high molecular weight polyethylene fiber. In addition, the cooling rate also has an impact on its performance.

Claims

1. A method for preparing ultra-high molecular weight polyethylene, characterized in that: The following steps are involved: (1) Seal the reactor and replace the air in the reactor with nitrogen, repeat the replacement 3-5 times, and add 65-70% of the reactor volume of hexane into the reactor in advance; (2) Adding the supported binuclear catalyst and methylaluminoxane into the reactor under stirring at 450-540 rpm; (3) Raise the temperature to 73-78°C, introduce ethylene gas through the feed port, maintain the pressure in the reactor at 0.4-0.8 MPaG, and continue the reaction for 4-5 hours; (4) After the reaction is completed, stop introducing ethylene and cool the reactor at a rate of 10-30°C / h. After the reactor temperature drops to room temperature, discharge the reaction product into a separation device and separate the ultra-high molecular weight polyethylene from the hexane by filtration. (5) Dry the separated ultra-high molecular weight polyethylene in a vacuum drying oven at a drying temperature of 65-75°C for a drying time of 18-20 hours to obtain pure ultra-high molecular weight polyethylene.

2. The method for preparing ultra-high molecular weight polyethylene according to claim 1, characterized in that: The method for preparing the supported binuclear catalyst comprises the following steps: a. Under nitrogen atmosphere, stir the material according to the mass ratio of imidazole to toluene of 1: (6-8) to completely dissolve the imidazole to form a uniform solution, then add isopropyl titanate and zirconium tetrachloride thereto, control the temperature at 25-28°C during the process, and continue stirring for 4-5h. The mass ratio of isopropyl titanate to zirconium tetrachloride is (1-2):1; b. triethylamine is added to the solution obtained in step a, the temperature is raised to 45-55 ° C, and stirring is continued for 2-4h. The amount of triethylamine added is 0.2-0.4 times the total mass of isopropyl titanate and zirconium tetrachloride; c. Add methylaluminoxane to the reaction system obtained in step b, continue stirring, then add silica, raise the temperature to 65-75°C, react for 4-8h under stirring at a stirring speed of 350-450rpm to fully activate the catalyst precursor and load it on the silica; d. After the reaction is completed, the reaction solution is cooled to room temperature, filtered under nitrogen protection, the solid product is washed 3-5 times with dry n-hexane, and the solid catalyst is dried in a vacuum drying oven at 55-65°C for 8-10h to obtain a supported binuclear catalyst.

3. The method for preparing ultra-high molecular weight polyethylene according to claim 2, characterized in that: In the step (2), the molar ratio of Al in methylaluminoxane to the metal in the supported binuclear catalyst is (80-120):1; in the step c, the amount of methylaluminoxane added is 8-13 times the total mass of isopropyl titanate and zirconium tetrachloride, the silica is spherical, and the amount of silica added is 18-22% of the total mass of the catalyst reaction system.

4. The method for preparing ultra-high molecular weight polyethylene according to claim 2, characterized in that: The purity of the isopropyl titanate and zirconium tetrachloride is higher than 99%, and the purity of imidazole is higher than 98%.

5. An ultra-high molecular weight polyethylene, characterized in that The ultra-high molecular weight polyethylene is prepared by the preparation method of any one of claims 1 to 4.

6. Use of the ultra-high molecular weight polyethylene according to claim 5, characterized in that: Used for the preparation of ultra-high molecular weight polyethylene sheets and ultra-high molecular weight polyethylene fibers.

7. The use of ultra-high molecular weight polyethylene according to claim 6, characterized in that: The method for preparing the ultra-high molecular weight polyethylene sheet comprises the following steps: ① Add ultra-high molecular weight polyethylene, antioxidant 1010 and zinc stearate into a mixer and mix them. The mixer speed is 900-1300 rpm. The mixing time is 10-20 minutes. The amount of antioxidant 1010 added is 0.2-0.4% of the mass of ultra-high molecular weight polyethylene, and the amount of zinc stearate added is 0.5-0.8% of the mass of ultra-high molecular weight polyethylene. ② Use a cold press molding machine for preforming, press the raw materials mixed in step ① into a blank of the desired shape, the density of the blank is 0.9-1.0g / cm³, the applied pressure is 8-10MPa, and the holding time is 5-10min; ③ Use a hot press for molding, the molding temperature is 180-220℃, the molding pressure is 10-30MPa, and the molding time is 3-5min per millimeter of thickness; ④ After the molding is completed, the mold is cooled by air cooling, and the cooling rate is controlled at 5-10℃ / min. When the product temperature drops to 65-75℃, demolding is carried out to obtain an ultra-high molecular weight polyethylene sheet.

8. The use of ultra-high molecular weight polyethylene according to claim 6, characterized in that: The method for preparing the ultra-high molecular weight polyethylene fiber comprises the following steps: Ⅰ. Add ultra-high molecular weight polyethylene, 4,4'-thiol methylene diphenol, 2,4-dimethylthiophenol, calcium stearate, titanate coupling agent, tri(2-methylpropyl) phosphate, polytetrafluoroethylene, 4-cyanostyrene, polypropylene and solvent decalin into a high-speed mixer and mix at a mixing speed of 1450-1550 rpm for 35-45 minutes; Ⅱ. The raw materials mixed in step Ⅰ are placed in a twin-screw extruder for extrusion, the extruder temperature is controlled at 213-218 ° C, the screw speed is 48-55rpm, and then filtered through a filter, and then fed into the spinning box by a metering pump to obtain a spinning solution, and the spinning solution temperature is controlled at 213-218 ° C; Ⅲ. The spinning solution in step Ⅱ is ejected from the spinneret hole to form a fiber, the spinneret aperture is 0.3-0.4mm, the spinning speed is 210-280m / min, the drafting multiple is 18-25 times, the drafting temperature is 152-158°C, and the decalin is blown off the fiber with 80°C nitrogen, and the fiber enters the hot air box for drying; IV. The fiber obtained in step III is stretched on a stretching machine at a stretching temperature of 145-155°C and a stretching ratio of 42-55 times to obtain an ultra-high molecular weight polyethylene fiber.

9. The use of ultra-high molecular weight polyethylene according to claim 8, characterized in that: In the step I, the mass fractions of the raw materials are: 100 parts of ultra-high molecular weight polyethylene; 0.5-1.3 parts of 4,4'-thiol methylene diphenol; 0.8-1.2 parts of 2,4-dimethylthiophenol; 1-3 parts of calcium stearate; 0.3-0.8 parts of titanate coupling agent; 2-3 parts of tri(2-methylpropyl) phosphate; 3-5 parts of polytetrafluoroethylene; 0.8-1.4 parts of 4-cyanostyrene; 8-12 parts of polypropylene; and 350-420 parts of decalin.

10. The use of ultra-high molecular weight polyethylene according to claim 8, characterized in that: A solvent recovery device is arranged above the twin-screw extruder, and the titanate coupling agent is one of triisostearyl isopropyl titanate or tetrabutyl titanate.

Citation Information

Patent Citations

  • Imidazole side chain half-metallocene imine ligand, and method and application thereof

    CN102659682A

  • Dissimilar metal binuclear catalyst and preparation method, composition and application thereof

    CN114933665A

  • Composition for preventing bedsores containing pumpkin seed component and external preparation containing same

    KR1020230158688A